Root cause analysis methodology for circuit breaker associated to GIS. (September 2020) - Arias Velásquez, Ricardo Manuel; Mejía Lara, Jennifer Vanessa
Highlights: Circuit breakers are vulnerable equipment due to current failures extinction and arcs. A new methodology for root cause analysis associated to circuit breaker. A real case study has been developed with 1023 circuit breakers. Abstract: In the last years, the most vulnerable equipment is the circuit breaker in the high voltage substation, due to dynamic behavior, associated to the extinction of electric arcs. Several studies have provided assessment methodologies, according to international standards as IEC, IEEE, CIGRE, and others; however, they are independent studies from the manufacturer's point of view, for the exchange of parts, not early detection, avoiding the fault. Our findings are a new methodology of engineering failure analysis is proposed for to avoid the sudden and catastrophic failure of the circuit breaker. Besides, to promote uniformity in the failure analysis of circuit breaker and the systematic and uniform collection of valuable data and information, in order to avoid its loss or destruction; with an early detection with the integration of the international standards.